Fat What no one is telling you - WGBH (Television station: Boston, Mass.); WGBH Educational Foundation (Boston, Mass. : WGBH Boston Video [distributor], 2008)
Fat : what no one else is telling you explains our psychological responses to food, shares new scientific knowledge about hunger, eating, and human metabolic operation. Shows how external pressures such as oversized restaurant portions and the unending barrage of food advertisements make fighting fat so difficult. Also features real Americans telling their stories about the biological barriers, cultural habits, and economic realities contributing to their struggle to get fit.
[pt. 4] Fat : what no one is telling you --
Title from container.
Special features: bonus interview footage with journalist and cancer survivor Linda Ellerbee, heart disease survivor Larry King, and more; printable resources such as heart-healthy recipes and 100 Ways to Eat Healthier; access to program Web sites; Spanish audio tracks and subtitles for Depression and FAT and closed captions.
DVD; Region 1; full screen presentation; Dolby Digital.
Keywords: Obesity